Modeling the fecal coliform footprint in a Lake Michigan urban coastal area. (September 2017) - Bravo, Hector R.; McLellan, Sandra L.; Klump, J. Val; Hamidi, Sajad A.; Talarczyk, Daniel
Abstract: The fecal coliform footprint in a Lake Michigan urban coastal area was studied using field sampling and modeling. Testing for fecal indicator bacteria at large spatial scales is not feasible after rain events; therefore it is desirable to develop a predictive model. A whole-lake model/nested model provided sufficient spatial and temporal resolution, simulated the appropriate transport mechanisms, and was verified against measurements. The major limitation of modeling watershed inputs is that there is no feasible continuous measurement of bacteria, which was addressed by developing a robust correlation between flow and bacteria concentrations. Field data and model predictions verified that most of the mixing between river and lake water occurs inside the harbor breakwater. Measurements and model results showed that the footprint can extend up to 8 km into the lake during sewer overflow events, depending on the meteorology that drives the interaction between tributary loads, whole-lake, and local circulation. Highlights: Fecal coliform footprint in coastal area was studied using field data and modeling. Bacteria loading time series developed from flow-bacteria concentration correlation. Model simulates appropriate transport mechanisms and was verified against field data. Extent of footprint depends on strengths of tributary flows and alongshore currents.